Dynamic response properties of polymer bonded explosives under different excitation by deceleration. (August 2021) - Xu, Wenzheng; Guo, Fengwei; Liang, Xin; Yan, Tianlun; Xu, Yang; Deng, Jie; Li, Yuexin; Wang, Jingyu
Graphical abstract: Highlights: An experimental method that can achieve different deceleration was designed. A constitutive model was developed to describe the dynamic response of the PBX. The material parameters of the HMX/F2602 were obtained. The dynamic response of PBX was studied from macroscopic and mesoscopic perspectives. Abstract: Based on the experimental method of projectile penetration into the concrete target, different excitation by deceleration of polymer bonded explosives (PBXs) was achieved by controlling the length of steel pillars behind PBXs. A series of impact tests were conducted to study the mechanical response of PBXs with different initial densities under different excitation by deceleration. A physical model was developed to describe the viscoelastic-plastic deformation of PBXs. The plastic part was added on the basis of the viscoelastic statistical crack mechanical model (Visco-SCRAM) model, and the compaction behavior of charge in different environments was characterized based on the Heckel compaction equation. The model was implemented in LS-DYNA, and the simulation results were verified by the experiments. The dynamic mechanical behavior of PBXs under different excitation by deceleration was studied from the macroscopic and mesoscale aspects. The stress curves, strain curves, the density change and the interaction between particles in deceleration environment were predicted. After comparison and analysis, the dynamic response law of the charge in the penetrating process was obtained. Macroscopic responses along with mesoscale modeling results are significantly important to have a better understanding of deformation mechanisms of PBXs.